Refining Lunar Trajectory Design: Software enhancement in the 'To The Moon' module of the CTK Platform (2024)
ABSTRACT : In the current context, marked by a growing interest from new countries in space missions and increased participation from both public and private institutions, Continuum Space Systems is a company that provides space navigation tools for entities in the aerospace sector. In response to this dynamic landscape, which sees a rising interest from new players in conducting space missions, particularly directed towards the Moon, this work focuses on direct lunar transfer, which has been used so frequently in lunar missions from Earth, specifically concentrating on departures where the satellite already has an initial lunar transfer impulse provided by an external source such as a launcher. The development and methodology for integrating this capability into Continuum's CTK platform are described. Using GMAT, an initial prototype mission model was generated, employing strategies such as pointing using the B-plane and optimizing the total delta-V in the lunar injection maneuver. The results show consistency with reference data using the same departure method (between 0.6 - 1 km/s of delta-V), and reveal a correlation between the departure date and the arrival inclination with respect to the lunar equator, where higher inclination angles imply lower required delta-V, reflecting appropriate behavior of the results. Additionally, improvements were made to the "To The Moon" module of CTK, providing informative messages for better understanding and analysis of the results, benefiting the platform's users. This study contributes to the advancement of the "To The Moon" module and expands the possibilities of CTK usage, with direct lunar transfer being a conventional method widely used to reach the Moon.